PERAN PERBANKAN SYARIAH DALAM MEMBANTU USAHA MIKRO KECIL DAN MENENGAH MENERAPKAN KONSISTENSI PENCATATAAN - AGUSTINA MELIA NURBAITI; Muhammad Iqbal Fasa (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2021)
This research is a follow-up study of articles (Deni Darmawati and Yuana Jatu Nilawati 2018) in accordance with the suggestions presented in her research entitled "The Role of Banking in Encouraging Micro, Small, and Medium Enterprises in the Application of Financial Accounting Standards for Micro, Small and Medium Entities" for the next researcher to provide an overview of the interest of MSMEs in the application of SAK EMKM and the role of banks in encouraging the implementation of SA EMKM. It should be noted that this study did not include the two external variables previously discussed, namely the Credit Scheme, Interest in Implementing SAK EMKM because of the limitations of the authors in obtaining data and information to examine these two external variables. In this study also emphasizes the interest of MSMEs in recording financial reports and the role of Islamic banks as partners of MSMEs.Islamic Bank as an additional hand of financial institutions that strive to become an intermediary institution in encouraging the economy of micro, small and medium enterprises by providing capital, training and motivation to MSMEs so that they can foster knowledge in disciplined financial recording.